Implementation of the e-Gampong Village Information System in Efforts to Improve the Quality of Public Services: Penerapan Sistem Informasi Desa e-Gampong dalam Upaya Meningkatkan Kualitas Layanan Publik - Safrizal Razali; Yuwaldy Away; Maimun; Aulia Rahman; Muslimsyah; Yudha Nurdin; Al Bahri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Efforts to enhance the quality of public services in Gampong Lam Ara, Aceh Province, were carried out through the development of a village information system (e-Gampong) and training for Gampong officials. Quality public services are considered crucial in evaluating government performance and creating a positive image in the eyes of the community. In an effort to provide more efficient and effective services, e-Gampong was developed to manage population data and other necessary administrative processes for the residents of Gampong Lam Ara. Additionally, intensive training was provided to Gampong officials to enhance their understanding of the smart village concept, Gampong management, Gampong digitization, and the utilization of e-Gampong. Evaluation results indicated that the implementation of the village information system and the training provided successfully improved the understanding and perceptions of Gampong Lam Ara officials and received a positive response from them. These results demonstrate that this approach succeeded in enhancing the quality potency of public services in Gampong Lam Ara and establishing a stronger foundation for realizing a smart village.